2005
DOI: 10.1021/np050157a
|View full text |Cite
|
Sign up to set email alerts
|

Iminosugar-Producing Thai Medicinal Plants

Abstract: Alpha-1-C-hydroxymethylfagomine (7), 3-O-beta-D-glucopyranosyl-DMDP (12), and 2,5-dideoxy-2,5-imino-D-glucitol (13) were isolated from the Thai traditional crude drug "Non tai yak" (Stemona tuberosa), which also contains a high concentration level of alpha-homonojirimycin (0.1% dry weight). "Thopthaep" (Connarus ferrugineus) and "Cha em thai" (Albizia myriophylla) contained 1-deoxymannojirimycin (DMJ) (10) at levels of 0.083% (dry weight) and 0.17% (dry weight), respectively. 2-O-alpha-D-Galactopyranosyl-DMJ (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Carefully planned extraction procedures have recently uncovered more examples of glycosyl iminosugars isolated from natural sources, thus indicating that their occurrence in Nature is not uncommon. [14] In contrast, few syntheses of glycosyl iminosugars are reported in the literature, [15,16] and they all reflect some difficulties in targeting the final compounds with good yields and selectivities, particularly in the glucosylation step. Interestingly, their inhibitory properties differ substantially from those of the parent iminosugar, with the linked carbohydrate moiety usually generating higher selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Carefully planned extraction procedures have recently uncovered more examples of glycosyl iminosugars isolated from natural sources, thus indicating that their occurrence in Nature is not uncommon. [14] In contrast, few syntheses of glycosyl iminosugars are reported in the literature, [15,16] and they all reflect some difficulties in targeting the final compounds with good yields and selectivities, particularly in the glucosylation step. Interestingly, their inhibitory properties differ substantially from those of the parent iminosugar, with the linked carbohydrate moiety usually generating higher selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Our present finding is in accordance with previous clinical study, in which a mouthwash of A. myriophylla was shown to significantly reduce mutans streptococci counts in saliva of schoolchildren (Cholticha et al, 2006). Previous phytochemical studies have revealed the presence of phenolic acids, iminosugars, triterpene saponins, lignan glycosides, and alkaloids (Ito et al, 1994;Yoshikawa et al, 2002;Asano et al, 2005;Panmei et al, 2007). Some of these chemical groups such as phenolics and alkaloids have been established to be the major phytochemical classes of antibacterial metabolites (Samy & Gopalakrishnakone, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, in the later studies, DGDP was found to be a weak inhibitor of α-and β-glucosidases (IC 50 300 to 1000 µM). [10] Figure 1. Representative structures of naturally occurring iminosugars.…”
Section: Natural Occurrence Of Pyrrolidine-containing Iminosugarsmentioning
confidence: 99%
“…Other notable pyrrolidines include codonopsine (5) and codonopsinine (6), first isolated in 1969 from Codonopsis clematidea, [14] and the radicamines A (7) and B (8), recently isolated from Lobelia chinensis LOUR. [15] Of the bicyclic pyrrolidine-containing iminosugars, representative examples include the pyrrolizidine casuarine (9), [16] and the indolizidine swainsonine (10), the first bicyclic alkaloid to be discovered. Due to its ability to competitively inhibit α-mannosidase II, swainsonine is currently being investigated for the treatment of cancer.…”
Section: Natural Occurrence Of Pyrrolidine-containing Iminosugarsmentioning
confidence: 99%